Effect of early intravenous heparin on coronary patency, infarct size, and bleeding complications after alteplase thrombolysis: results of a randomised double blind European Cooperative Study Group trial. Issue 2 (February 1992) - de Bono, D P; Simoons, M L; Tijssen, J; Arnold, A E; Betriu, A; Burgersdijk, C; López Bescos, L; Mueller, E; Pfisterer, M; Van de Werf, F
Abstract : OBJECTIVE–To determine whether concomitant treatment with intravenous heparin affects coronary patency and outcome in patients treated with alteplase thrombolysis for acute myocardial infarction. DESIGN–Double blind randomised trial. TREATMENT REGIMENS–Alteplase 100 mg (not weight adjusted) plus aspirin (250 mg intravenously followed by 75-125 mg on alternate days) plus heparin (5000 units intravenously followed by 1000 units hourly without dose adjustment) was compared with alteplase plus aspirin plus placebo for heparin. SETTING–19 cardiac centres in six European countries. SUBJECTS–652 patients aged 21-70 years with clinical and electrocardiographic features of infarcting myocardium in whom thrombolytic therapy could be started within six hours of the onset of major symptoms. MAIN OUTCOME MEASURE–Angiographic coronary patency 48-120 hours after randomisation. RESULTS–Coronary patency (TIMI grades 2 or 3) was 83.4% in the heparin group and 74.7% in the group given placebo for heparin. The relative risk of an occluded vessel in the heparin treated group was 0.66 (95% confidence interval 0.47 to 0.93). Mortality was the same in both groups. There were non-significant trends towards a smaller enzymatic infarct size and a higher incidence of bleeding complications in the group treated with heparin. CONCLUSIONS–Concomitant intravenous heparin improves coronary patency in patients with alteplase. Whether this can be translated into improved clinical benefit needs to be to be tested in a larger trial.